The Critical Role of Knowledge Creation on Achieving the Competitive Advantages In Algerian Industrial Organizations - Bentata, Atika (The Arab Journal of Administration, 2023)
This study aimed at identifying the effect of knowledge creation on achieving the Competitive Advantages in Algerian Industrial Organisations. A questionnaire was developed and distributed, which consist of (142) subjects, (97) questionnaire of which were returned and analyzed. Validity and reliability of questionnaires were computed. The results of the study refer to significant statistical effect of knowledge creation on achieving the competitive advantages in the organisations sample study. The study also shows that all correlations were statistically significant between the knowledge creation and achieving the competitive advantages and its various dimensions, and the correlations came between them to varying degree. In the light of the findings; some recommendations are given such as: ensuring full freedom for employees to create new ideas and knowledge to add to their available stock of knowledge, and thus harness them to strengthen their competitiveness.